Passage through the carotid sheath: An alternative path to the pre-spinal route for direct repair of contralateral C7 to the lower trunk in total brachial plexus root avulsion injury - Piyush Bhupendra Doshi; Yogesh Chimanbhai Bhatt (Indian Journal of Plastic Surgery)
Context: In surgical management of global brachial plexus injuries, direct repair of contralateral C7 (cC7) to the anterior division of the lower trunk, can produce good extrinsic finger flexion. The pitfalls associated with the pre-spinal passage have, perhaps, proved to be a deterrent for using this technique routinely. Aims: The aim of this study is to demonstrate an alternative to pre-spinal route for cC7 transfer in brachial plexus avulsion injuries. Methods: We noted that the mobilised lower trunk, which reaches the level of the scalenus anterior by passage deep to the clavicle, can be brought to the suprasternal notch when brought out from below the clavicle. This area was dissected in two cadavres, and safe passage was found through the carotid sheath with the common carotid artery medially and the internal jugular vein with the vagus nerve laterally. The cC7 root dissected medial to the scalenus anterior muscle can be directly transferred along this path to the subcutaneous plane at the suprasternal notch. This study allowed us to execute a direct repair in ten clinical cases of global brachial plexus injuries. In each case, the passage was prepared rapidly and uneventfully. The repair was technically simple and could be performed comfortably using suitable fine suture materials. In none of these cases, did we need to shorten the humerus. Results: The clinical outcome of this technique is awaited. Conclusions: We advocate carotid sheath route to approximate the cC7 to the injured lower trunk in global palsies, as the risks associated with the pre-spinal route can be readily avoided.